Analisis Strategi Usaha Sayuran Hidroponik Pada Masa Pandemi Covid-19 di Kota Makassar (Studi Kasus di Green Top Farm) - Nur Indah Waliyanti; Jusni; Pipi Diansari (Jurnal Sosial Ekonomi Pertanian, 2022)
This research aims to analyze strategies that can be used in hydroponic vegetable business at Green Top Farm. This research method uses SWOT analysis. Determination of the research location by purposive. Informants in this study consisted of main informants and key informants. Data used are primary and secondary. The results showed that the Green Top Farm IFE matrix was able to take advantage of strengths to overcome weaknesses with a value of 2.40. While the EFE matrix shows that the Green Top Farm can take advantage of opportunities and be able to anticipate threats with a value of 2.18. The SWOT matrix shows that Green Top Farm is in quadrant I, namely the SO (Strength–Opportunities) strategy. The strategy formulation produces alternative strategies that are in accordance with the company's circumstances, namely expanding the hydroponic vegetable market, increasing the production and quality of hydroponic vegetables and maximizing the use of information technology to market products.